Implementation of Waste Management Policy in South Tangerang City from the Perspective of Environmental Law and the Effectiveness of Law Enforcement - Yusup, Muhamad; Panjaitan, Paris; Sadikin, Mohamad; M, Mentari; Sitorus, Novandrik Yeriko; Suryani, N. Lilis (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Waste management in South Tangerang City has become an increasingly complex environmental issue along with population growth and urbanization. Although various regulations are already in place, such as Law Number 18 of 2008 and related regional regulations, the implementation of waste management policies still faces numerous challenges, including issues related to legal substance, law enforcement structure, and the legal culture of the community. This Community Service Program (PKM) aims to analyze the implementation of waste management policies from an environmental law perspective and to evaluate the effectiveness of law enforcement in South Tangerang City. The method used is a normative-empirical approach, with activities including seminars, interactive discussions, and workshops involving the community and stakeholders. The findings indicate a gap between preventive regulations and the reality in the field, which remains largely reactive. The main factors contributing to the low effectiveness of law enforcement include limited facilities and infrastructure, weak supervision, and low public awareness regarding waste management. Through this activity, it is expected that public understanding of the importance of environmentally based waste management will increase, along with greater active participation in preserving environmental sustainability. In addition, strengthening derivative regulations, optimizing law enforcement, and implementing technology-based and community-based waste management systems are necessary to achieve effective and sustainable waste management.